Predicted facies, sedimentary structures and potential resources of Jurassic petroleum complex in S-E Western Siberia (based on well logging data) - Prakojo, Feliks Santo; Lobova, Galina Anatolyevna; Abramova, Raisa Nikolaevna (IOP Publishing, 2015)
This paper is devoted to the current problem in petroleum geology and geophysics- prediction of facies sediments for further evaluation of productive layers. Applying the acoustic method and the characterizing sedimentary structure for each coastal-marine-delta type was determined. The summary of sedimentary structure characteristics and reservoir properties (porosity and permeability) of typical facies were described. Logging models SP, EL and GR (configuration, curve range) in interpreting geophysical data for each litho-facies were identified. According to geophysical characteristics these sediments can be classified as coastal-marine-delta. Prediction models for potential Jurassic oil-gas bearing complexes (horizon J[1]{1}) in one S-E Western Siberian deposit were conducted. Comparing forecasting to actual testing data of layer J[1]{1} showed that the prediction is about 85%.
Keywords: фации; осадочные структуры; ресурсы; нефтяная геология; продуктивные пласты; геофизические характеристики; прогнозирование